Physical performance and evidence of fatigue in Rugby Sevens referees - Portillo, L. J.; Suarez-Arrones, L.; Sanchez M.; Sanchez, F.; Nunez, F. J.; Garcia, J. M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The aims of this study was to examine changes in running demands and effects of fatigue in elite referees during the competition of rugby sevens tournament. METHODS. A prospective and observational study design was used to assess physical demands of 7 elite referees in 21 competition matches. Timemotion analysis of running activity was collected using Global Positioning System (GPS, SPI Pro X 15Hz) and HR monitors. RESULTS: Mean total distance (± SD) covered over the whole match by referees was 108.5 ± 9.5 m/min. The number of sprint during the match was 6,1 ± 3,1 with rank from 1 to 13 sprints. The distance of high-speed zone (> 20 km/h) was 18.6 ± 6.5 m. with rank from 7 to 74.4 m. The referees spent most of their match time at HR intensities between 81- 90% HRmax with significant differences (P < 0.05).The fatigue in matches have been analyzed considering information by quarters. Whole match is divided in four quarters and therefore each half has two. There was a significantly reduction in traveled distance between first quarter and second quarter of both halves (P < 0.01). When the three tournament matches were analyzed total distance decreased significantly between first and last match (P < 0.01). Mean distance of sprinting decreased significantly (P < 0.05). Also the peak of maximum speed decreased between first and last match (P > 0.05). DISCUSSION: There are substantial differences around the development of the physical demands of referees during the matches in rugby sevens tournament. Running demands of referees investigated in this study are higher than other types of rugby (Kay & Gill, 2003; Martin et al., 2001) and similar to the rugby sevens players (Suarez-Arrones et al., 2011a ; 2011b). This study has reported running demands in rugby sevens referee. Running speed is higher than other modalities such as rugby union. Study findings can be used as a reference value to adapt specific training programs for rugby sevens referees.